Immunophenotypic Analysis of B Lymphocytes in Patients with Common Variable Immunodeficiency: Identification of CD23 as a Useful Marker in the Definition of the Disease. (4th April 2013) - Patuzzo, Giuseppe; Mazzi, Filippo; Vella, Antonio; Ortolani, Riccardo; Barbieri, Alessandro; Tinazzi, Elisa; Marchi, Giacomo; Codella, Orazio; Beri, Ruggero; Puccetti, Antonio; Lunardi, Claudio
Abstract : Common variable immunodeficiency (CVID) is a primary immunodeficiency characterized by the failure of B lymphocytes differentiation leading to deficient immunoglobulins secretion. The identified genetic defects account only for a minority of cases. The importance of B cells immunophenotyping in the classification of CVID is known. This procedure can identify alterations on the cell surface molecules expression that could explain some immunological disorders characteristic of CVID. Moreover, some immunophenotypical aspects can correlate with clinical features of the disease. We used this procedure to analyze a cohort of 23 patients affected by CVID, in order to identify the novel alterations of B cells and to find the possible correlations with clinical features. Circulating B cells were studied by flow cytometry incubating whole blood with specific antibodies for B cell surface molecules including CD27, IgM, IgD, CD21, and CD23. We compared the population of "switched memory" IgD− CD27+ B lymphocytes with the population of "switched memory" IgM− IgD− CD23− CD27+ B cells. These last B cells were reduced in patients compared to healthy controls; moreover, IgM− IgD− CD23− CD27+ B cells were lower than IgD− CD27+ B cells in patients with CVID. The reduction of this subset of B lymphocytes correlates more tightly than IgD− CD27+ B cells with lymphadenopathy and airways infections. In conclusion, our findings may help in better identifying patients with CVID.